COLOURISM AS A CATALYST FOR THE SKIN WHITENING INDUSTRY IN THAILAND - Alexander Franco; Scott S. Roach (Malaysian Journal of Business and Economics (MJBE), 2023)
Colorism is a historical and cultural phenomenon with global dimensions. This phenomenon is credited, in part, for the growth and financial success of the skin-lightening industry throughout the world. In Thailand, dark skin is often associated with lower-income classes, including farm labor. As a pioneering effort, this study sought to empirically identify colorism in a way that would minimize social desirability bias. Three groups in an MBA program at an international university in Bangkok - Thais with Chinese ancestry, non-Chinese Thais, and non-Thai foreigners – were asked to identify socio-economic status (“rich” or “poor”) by examining photographs of male and female Thais with dark, medium, and light skin tones. An analysis was conducted using the demographic variables of ethnicity, gender, and age. The study found significant differences wherein Thai-Chinese associated light skin tone with wealth and dark skin tone with poverty. Non-Chinese Thais followed in this assessment, but foreigners did not. Regarding marriage, both Thai-Chinese and non-Chinese Thais chose photographs of individuals with light skin to marry, but they were significantly different than the foreigners where skin tone was not a factor. There was no significant difference regarding gender. However, age was significant in that the younger group in the study (ages 20 to 27) identified dark skin tones as indicating poverty more than the older group in the study (ages 28 to 48).